Study on the preparation process and performance of a conductive, flexible, and transparent wood - Lechen Yang (Elsevier, 2021)
As one of the most sustainable resources, wood has been widely used in the fields of construction, decoration, flooring and furniture. The emergence of transparent wood further expands the application fields of wood to solar cells, luminescent magnetic switches, artificial electronic skins and stress sensors. However, most of the transparent woods reported are obtained by impregnating resins such as polymethylmethacrylate (PMMA), epoxy resin (EP) and polyvinylpyrrolidone (PVP). Here, we demonstrated a flexible transparent wood prepared based on a deep eutectic solvent composed of acrylic acid and choline chloride. The light-absorbing chromophore group of natural wood was removed by the sodium chlorite delignification method to obtain the treated wood template, then the deep eutectic solvent was infiltrated into the wood template, and the final transparent wood was obtained by photo-initiated polymerization. This transparent wood has excellent stretchability (maximum tensile strain up to 73.9%), flexibility and tensile resilience. Moreover, this transparent wood also has good electrical conductivity and temperature sensing properties. The electrical signal of transparent wood has very favorable stability and repeatability in multiple heating–cooling cycles, indicating its great potential as a temperature sensor.